Pengaruh Price, Online Customer Review, Online Customer Rating, Dan Kemudahan Penggunaan Terhadap Keputusan Pembelian Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2020 Pengguna Platform Shopee - Cahyanto, Septian Dwi; Rachma, N.; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to determine and analyze the influence of price, online customer reviews, online customer ratings and ease of use simultaneously and partially on purchasing decisions among 2020 Islamic University of Malang FEB students using the Shopee platform. The population in the research is the unknown number of users of the Shopee application within the FEB Islamic University of Malang, class of 2020. The approach method uses a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 105 respondents and using the SPSS analysis tool. The results of the research show that price, online customer reviews, online customer ratings and ease of use simultaneously influence purchasing decisions among 2020 Islamic University of Malang FEB students who use the Shopee platform and partially price, online customer reviews and ease of use influence purchasing decisions among students. FEB Islamic University of Malang class of 2020 users of the Shopee platform but online customer ratings have no influence on purchasing decisions among students of FEB Islamic University of Malang class of 2020 users of the Shopee platform. Keywords : Price, Online Customer Review, Online Customer Rating, Ease of Use, Purchase Decision